2017
DOI: 10.1080/13632469.2017.1342302
|View full text |Cite
|
Sign up to set email alerts
|

A Ground Motion Record Selection Approach Based on Multiobjective Optimization

Abstract: The evaluation of the seismic safety and reliability of buildings and building contents within a probabilistic framework often requires response history analyses using site-specific ground motion records. The ground motion selection method proposed in this paper addresses this issue by a stochastic search procedure in which record sets are selected such that firstand second-order statistics (median and dispersion) satisfy predefined ground motion spectrum targets over a wide period range. Once a ground motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…In this paper, 202 ground motion records are selected for the selected site from PEER ground motion database [25]. The following criteria are considered in the preselection of records: -Moment Magnitude of 5.5 to 7.9, -Shear velocity for soil type C (very dense soil and soft rock) based on ASCE 7-16 [24]: 366 ≤ v s ≤ 762, -The focal distance of 0 to 80 km as suggested in other studies ( [11,26]), -Acceleration spectral ordinates are obtained for damping ratio of 5 %.…”
Section: Pesa-iimentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, 202 ground motion records are selected for the selected site from PEER ground motion database [25]. The following criteria are considered in the preselection of records: -Moment Magnitude of 5.5 to 7.9, -Shear velocity for soil type C (very dense soil and soft rock) based on ASCE 7-16 [24]: 366 ≤ v s ≤ 762, -The focal distance of 0 to 80 km as suggested in other studies ( [11,26]), -Acceleration spectral ordinates are obtained for damping ratio of 5 %.…”
Section: Pesa-iimentioning
confidence: 99%
“…One of the major advances of their suggested tool is the possibility to compute the Conditional Mean Spectrum (CMS) for the European territory. Moschen et al [11] used a multi objective algorithm to select and scale earthquake records to match a target median spectrum and a target dispersion spectrum over a predefined period (or frequency) range. Shahrouzi [12] introduced Opposition-Switching Search for the spectral matching of ground motions and showed that results obtained by the proposed algorithm are better than PSO algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, an analytical relation for the parameter dependent NPA demand is determined for the Century City record set [15], which consists of 92 ground motions of the PEER ground motion database [16]. These records have been selected using a multi-objective optimization prodecure by minimizing two fitness functions.…”
Section: Normalized Peak Acceleration Demand For the Century City Recmentioning
confidence: 99%
“…Figure 6 shows the target spectra (bold black lines), the 92 individual response spectra (gray lines), and the corresponding statistical quantities (thin black lines) of the Century record set, which will be used for analyses in the remainder of this paper. For detailed information of the record selection procedure the reader is referred to [15,3]. Table 2 lists the corresponding coefficients for evaluation of Equation (10).…”
Section: Normalized Peak Acceleration Demand For the Century City Recmentioning
confidence: 99%
“…Kanai-Tajimi power spectral density (KT-PSD) (black line) fitted to the normalized median PSD of the ground motions (gray line) [12] dispersion of the record set match this design response spectrum and a target dispersion of σ t = 0.80 in the frequency range of 0.33 Hz ≤ ω /2π ≤ 20 Hz (i.e., the period range of 0.05 s ≤ T ≤ 3.00 s). The underlying evolutionary record selection algorithm is described in [14]. Additionally, Fig.…”
Section: Characterization Of the Seismic Excitationmentioning
confidence: 99%